2023
DOI: 10.1111/ene.15801
|View full text |Cite
|
Sign up to set email alerts
|

Sex hormones differentially contribute to Parkinson disease in males: A multimodal biomarker study

Abstract: Background and purpose: Parkinson disease (PD) presents relevant sex-related differences in epidemiology, pathophysiology, and clinical features, with males being more vulnerable to the disease. Sex hormones might have a role, as the experimental models suggest; however, human-based evidence is scarce. Here, we integrated multimodal biomarkers to investigate the relationships between circulating sex hormones and clinicalpathological features in male PD patients. Methods: A cohort of 63 male PD patients underwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The dopamine system contains a high density of oestrogen receptors, through which hormones exert their protective role on dopaminergic functions 35 . Such protective effects of oestrogens are achieved by reducing oxidative stress and mitochondrial dysfunction, limiting neuroinflammation, and preventing the deposition of α-synuclein and neural injury 36 . Another aspect under investigation is related to the detrimental role of GBA1 mutations on sphingolipid homeostasis, the latter found to be modulated by means of oestrogen receptor 37 .…”
Section: Discussionmentioning
confidence: 99%
“…The dopamine system contains a high density of oestrogen receptors, through which hormones exert their protective role on dopaminergic functions 35 . Such protective effects of oestrogens are achieved by reducing oxidative stress and mitochondrial dysfunction, limiting neuroinflammation, and preventing the deposition of α-synuclein and neural injury 36 . Another aspect under investigation is related to the detrimental role of GBA1 mutations on sphingolipid homeostasis, the latter found to be modulated by means of oestrogen receptor 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Although we have not a clear explanation for the higher frequency of NMF among women a possible role of sex hormones cannot be ruled out. As a matter of fact, preclinical studies have shown a possible neuroprotective role of estrogens and, according to literature evidence, lower levels are associated with a greater risk of developing motor fluctuations (Bovenzi et al 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Such fluctuations can be essentially related to hormonal changes, since estrogen and progesterone levels rise during pregnancy and dramatically drop with puerperium. While the neuroprotective and pro-dopaminergic effects of estradiol (E2) are well-known [30], the properties of estriol (E3), the dominant estrogen during pregnancy, and progesterone are not clear yet [17]. Apart from sex hormones, other factors, including altered pharmacokinetics, diet changes, and variations in intestinal absorption, as well as physical and psychosocial aspects, might also contribute to motor fluctuations during pregnancy [17].…”
Section: Discussionmentioning
confidence: 99%